Identifikasi Merkuri Pada Produk Pemutih di Kota Bekasi - Purwanti, Angki; Prasetyorini, Tri; Mujianto, Bagya (Jurnal Laboratorium Khatulistiwa, 2025)
The BPOM regulations prohibit the use of mercury in cosmetics. Previous studies have reported mercury compounds in illegal skin-whitening products widely used by the public. This study aimed to identify mercury in facial whitening products circulating in the districts of Pondok Gede, Pondok Melati, and Jatiasih in Bekasi City. The study also traced distribution sites and recorded the presence or absence of BPOM registration numbers on products containing mercury. A descriptive study was conducted on 25 brands of facial whitening products. Qualitative mercury analysis was carried out using KI, NaOH, and the amalgam test. Testing was conducted from July to December 2024 at the Chemistry Laboratory of Poltekkes Jakarta III. Samples were considered positive if all three tests showed indicative color changes. The results showed that 12 brands (48%) contained mercury, and none had BPOM registration numbers. These products were obtained from terminals (16%), drugstores (12%), markets (12%), and plazas (8%), with none found in pharmacies. Meanwhile, 13 brands (52%) did not contain mercury, and all had BPOM registration numbers. A correlation was observed between mercury content and the presence of BPOM registration numbers. In conclusion, illegal cosmetics require serious attention due to potential mercury contamination. Terminals, markets, drugstores, and plazas were common distribution sites for these products. Consumers are advised to check the BPOM registration number before purchasing facial whitening products.